Holey graphene-wrapped porous TiNb24O62 microparticles as high-performance intercalation pseudocapacitive anode materials for lithium-ion capacitors - Li, Shaohui (2018)
It is desirable to develop an energy storage system with both high energy density and high power density along with excellent cycling stability to meet practical application requirements. Lithium-ion capacitors (LICs) are very promising due to the combined merits of the high power density of electrochemical capacitors and the high energy density of batteries. However, the lack of high rate performance anode materials has been the major challenge of lithium-ion capacitors. Herein, we designed and synthesized holey graphene-wrapped porous TiNb24O62 as an anode material for lithium-ion capacitors. Pseudocapacitive storage behaviors with fast kinetics, high reversibility, and excellent cycling stability were demonstrated. The hybrid material can deliver a high capacity of 323 mAh g−1 at 0.1 A g−1, retaining 183 mAh g−1 at 10 A g−1. Coupled with a carbon nanosheet-based cathode, an LIC with an ultrahigh energy density of 103.9 Wh kg−1 was obtained, and it retained 28.9 Wh kg−1 even under a high power density of 17.9 kW kg−1 with a high capacity retention of 81.8% after 10,000 cycles.